2022
DOI: 10.1155/2022/8616535
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Deep Learning Mechanism for Predicting the Axillary Lymph Node Metastasis in Patients with Primary Breast Cancer

Abstract: The second largest cause of mortality worldwide is breast cancer, and it mostly occurs in women. Early diagnosis has improved further treatments and reduced the level of mortality. A unique deep learning algorithm is presented for predicting breast cancer in its early stages. This method utilizes numerous layers to retrieve significantly greater amounts of information from the source inputs. It could perform automatic quantitative evaluation of complicated image properties in the medical field and give greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The Kohonen self-organizing algorithms, feed forward, and radial basis functions are examples of assessment techniques for artificial neural networks. The outcomes of the study indicate that the deep learning model can more accurately assess the final diagnosis of the axillary lymph node metastatic from US imaging of initial breast cancer [ 42 ]. Kohonen’s artificial neural networks were also used to select new inhibitors of SARS-CoV-2 activator protein furin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kohonen self-organizing algorithms, feed forward, and radial basis functions are examples of assessment techniques for artificial neural networks. The outcomes of the study indicate that the deep learning model can more accurately assess the final diagnosis of the axillary lymph node metastatic from US imaging of initial breast cancer [ 42 ]. Kohonen’s artificial neural networks were also used to select new inhibitors of SARS-CoV-2 activator protein furin.…”
Section: Discussionmentioning
confidence: 99%
“…In the dermatologic study of Styła et al the dermatoscopic images were used to train Kohonen neural networks to provide fully automatic diagnostic systems capable of determining the type of pigmented skin lesion [ 48 ]. Referring to the above and recent studies, it was shown that machine learning algorithms, particularly Kohonen networks, might be useful in medicine and can improve diagnosis and give clinicians more tools in treatment planning [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. According to our study, we can recommend other specialists use Kohonen networks in their daily practice to ease the prediction of the progression of periodontitis with the usage of data: gender, age, active nicotinism, the number of teeth still present, the approximate plaque index (API), bleeding on probing (BoP), pocket depth (PD), and clinical attachment loss.…”
Section: Discussionmentioning
confidence: 99%
“…Other retrospective studies investigating the prediction of lymph node metastasis in breast cancer patients using ultrasound images and AI algorithms to evaluate the images prove more robust in their methodologies through enrolling larger numbers of patients into their training and validation sets. A study by Ashokkumar et al evaluated three different deep Artificial Neural Networks (ANNs)—one based on feed forward, one on radial basis function, and one on Kohonen self-organizing models—for use in predicting metastasis in pre-operative breast cancer patients and compared their performance against experienced radiologists ( 19 ). The study involved a total of 908 images from 750 patients for training the sets.…”
Section: Deep Learning In Ultrasound Computed Tomography and Magnetic...mentioning
confidence: 99%
“…Millions of people worldwide suffer from deadly breast cancer [1] Early detection and accurate diagnosis are crucial factors in improving the prognosis and overall survival rates of breast cancer patients. In recent years, the intersection of healthcare and data science has led to the development of novel techniques and methodologies aimed at enhancing the accuracy and efficiency of breast cancer detection [2]. One promising avenue in this endeavour is the application of DR techniques which are designed to reduce the complexity of high-dimensional data while preserving essential information [3].…”
Section: Introductionmentioning
confidence: 99%